If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -15 = 2x + -3 Reorder the terms: -15 + x = 2x + -3 Reorder the terms: -15 + x = -3 + 2x Solving -15 + x = -3 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -15 + x + -2x = -3 + 2x + -2x Combine like terms: x + -2x = -1x -15 + -1x = -3 + 2x + -2x Combine like terms: 2x + -2x = 0 -15 + -1x = -3 + 0 -15 + -1x = -3 Add '15' to each side of the equation. -15 + 15 + -1x = -3 + 15 Combine like terms: -15 + 15 = 0 0 + -1x = -3 + 15 -1x = -3 + 15 Combine like terms: -3 + 15 = 12 -1x = 12 Divide each side by '-1'. x = -12 Simplifying x = -12
| 5(x+2)-3=3x+15 | | -26+3=-39+14x | | -12(6x-5)= | | 5v^2+11v-42=0 | | 8(x+20)=10x | | xf=17 | | -72x+60= | | (X-3)2+(y-5)2=9 | | -80x+3= | | x+x+8+x+x+8=140 | | -80x+24= | | 13-2(-6+14)= | | 11x+2y=-21 | | -20=n+14 | | 6x^2+44x+70=0 | | 7-3(2x-5)= | | 2e^3x=15 | | y+7x=15 | | -8(10x-3)= | | 67+(-67)= | | -48=6n | | (x+2)(x-3)=-4 | | 3w-1=2w+10 | | 5x+11y=38 | | (6a^2+3a-4)+(-3a^2+2a+6)= | | 8x=2y+12 | | 2x+4=49-3x | | 5/8-(1/4)2 | | -7+-5y=0 | | 9.5x=-123.5 | | f(x)=17x | | 4x+12=5x-5 |